A Creative workspace in the City - Mpuisang, Thandeka (School of Architecture, Planning and Geomatics, 2016)
It is crucial to understand from the onset that although the following investigation is both about altering the very nature of a space physically (flexibilty) , (this is not the main focus) thus rendering it to multiple uses and configurations. This project is predominently about designing space within a building that the user and occupants can have a degree of control in their interpretation and use of the spaces. This is also not an argument for an anarchiac "anything goes", but instead suggests that space must be left in politics for difference and ambiguity to flourish within a shared background. This is an inside I outside approach to Architecture, that prioritises the pursuit of prioritizing spatiality in the project of architecture today and aims to define space less as a quantifiable object and more as an idea, a way of seeing, act of making and way of engaging culture and society. It is a reflective and critical process of discovering ways in which we can start designing unprogrammed space, loose space, inclusive space that supports social interaction and freedom of action in architecture today. The aim is to look briefly into the existing social spatial discourse , but also allowing the recognition of new ideas on spatiality that are taking root in contemporary discourse to surface. Using this information, I will explore how they can effectively be applied to architecture in the quest to imagine a new emergant spatial practice that reflects a new democratic order in a South African context.